Hush money - Parker, Robert B. (New York : G.P. Putnam's Sons, 1999)
PI Spenser investigates charges of discrimination made by a black professor who was denied tenure at a New England university. The professor claims there was a conspiracy to brand him as a homosexual. By the author The Godwulf Manuscript.
A Spenser novel.
88730
Keywords: Spenser (Fictitious character) -- Fiction; Private investigators -- Massachusetts -- Boston -- Fiction. -- Prejudice - racial; prejudice - homosexuality; Boston (Mass.) -- Fiction; Mystery fiction